Palimpsests of Themselves Logic and Commentary in Postclassical Muslim South Asia - Ahmed, Asad Q. (University of California Press, 2022)
Palimpsests of Themselves is an intervention in current discussions about the fate of philosophy in postclassical Islamic intellectual history. Asad Q. Ahmed uses as a case study the most advanced logic textbook of Muslim South Asia, The Ladder of the Sciences, presenting in English its first full translation and extended commentary. He offers detailed assessments of the technical contributions of the work, explores the social and institutional settings of the vast commentarial response it elicited, and develops a theory of the philosophical commentary that is internal to the tradition. These approaches to the commentarial text complicate presuppositions upon which questions of Islam's intellectual decline are erected. As such, Ahmed offers a unique and powerful opportunity to understand the transmission of knowledge across the Islamic world.